The Phonological Structure of Sundanese Language as a Representation of Regional Language Identity - Annisa Silvia; Otong setiawan Djuharie (Educational Journal, 2026)
This research aims to describe the phonological system of the Sundanese language and analyze how the characteristics of the sound function as a pillar of identity for the speaking community. As the regional language with the second largest number of speakers in Indonesia, Sundanese has a phonetic uniqueness that clearly distinguishes it from other cognate languages. Furthermore, in an ethnolinguistic perspective, the vowel 'eu' is analyzed as a symbol of the collective identity of the Sundanese people. The results show that the use of the vowel 'eu' is not just an articulatory phenomenon, but a representation of a "sense of language" rooted in local values. In the midst of modernization and the influence of urban Indonesian, this vowel is an indicator of the vitality of the language as well as a boundary marker for its speakers. This study concludes that the preservation of the vowel 'eu' in daily speech practice is an active effort to maintain the integrity of Sundanese language identity in the era of globalization.